Report from the international science conference Communication Research in the Era of Neo-Globalisation: Reorientations, Challenges and Changing Context, organized by International Association for Media and Communication Research, Beijing (China), 11-15.07.2022 - Leśniczak, Rafał (Folia Toruniensia, 2022)
On July 11-15, 2022, an international scientific conference “Communication Research in the Era of Neo-Globalisation: Reorientations, Challenges and Changing Contexts” took place in Beijing. The meeting was organized by the International Association for Media and Communication Research (IAMCR). The aim of the conference was to analyze the unprecedented challenges of new media and cultural topography in the post-pandemic era of volatility, uncertainty, complexity, and ambiguity, including but not limited to issues related to public health, climate change, and sustainable development. The main speakers of the conference were, among others, Prof. Manuel Castells (University of Southern California, USA), Prof. Changfeng Chen (Tsinghua University, China), Prof. Jantima Kheokao (Asian Network for Public Opinion Research, Thailand), Prof. Dadang Rahmat Hidayat (Padjadjaran University, Indonesia), Prof. Yu-li LIU (City University of Hong Kong, China).